Electronic states and metallic character of carbide Co/MoS2 catalytic interface - López-Galán, Oscar; Ramos Murillo, Manuel Antonio; Berhault, Gilles; Torres, Brenda; Chianelli, Russell R. (2021)
We report computer assisted density functional theory computations of electronic states in carbide Co9S8/MoS2 interface model. The interface model was previously proposed using crystallographic information from experimental high-resolution TEM observations; and directly observed by in-situ heating to confirm carbon deposit occurs at the sulfur edge of Co9S8/MoS2 which creates a thin carbide layer. In here, the total energy for carbon adsorption results eight times more favorable to occur at sulfur edge in comparison to molybdenum or cobalt replacement by permutation of carbon atoms as contained in C, CH, CH2 species by exothermic energies. Amorphous carbon excites 2pz orbitals as observed on density of states near Fermi level (FE), and 13% decreased in terms of charge carriers available, causing to decrease its chemical catalytic reactivity and bending ofMoS2 slabs as carbon starts to accumulate at the sulfur edge mainly, which is attributed to charge distribution around the adsorption site caused by the foreign atoms, confirmed by electron density plots, that acts as ‘electron traps’. This helps us concluding that carbon replacement can induce change of selectivity in direct desulfurization pathway.